2009
DOI: 10.1007/s11745-009-3304-8
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Palm Oil for Anti‐Inflammatory Nutraceutical Properties

Abstract: Palm oil is one of the most important edible oils in the world. Its composition (rich in palmitate and oleate) make it suitable for general food uses but its utility could be increased if its fatty acid quality could be varied. In this study, we have modified a palm olein fraction by transesterification with the n-3 polyunsaturated fatty acids, alpha-linolenate or eicosapentaenoic acid (EPA). Evaluation of the potential nutritional efficacy of the oils was made using chondrocyte culture systems which can be us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Interestingly, PO did not affect the expression of macrophage polarization markers but significantly reduced IL-6 and TNF-α production in the inflammatory M1 microenvironment (Figures 4 and 5). In this regard, several previous studies have demonstrated that palm oil has anti-inflammatory effects [40][41][42][43]. Those studies focused on specific components of palm oil, such as δ-tocotrienol, whereas we used whole palm oil in our high-fat diet-induced obese mice model.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, PO did not affect the expression of macrophage polarization markers but significantly reduced IL-6 and TNF-α production in the inflammatory M1 microenvironment (Figures 4 and 5). In this regard, several previous studies have demonstrated that palm oil has anti-inflammatory effects [40][41][42][43]. Those studies focused on specific components of palm oil, such as δ-tocotrienol, whereas we used whole palm oil in our high-fat diet-induced obese mice model.…”
Section: Discussionmentioning
confidence: 99%
“…These studies were largely focused on the efficiency of fish oil supplementation, which, in practice, is the supplementation of EPA-DHA combination. However, studies with individual fatty acids, or fatty acids in combinations other than EPA-DHA, such as fish oil-olive oil or EPA esterified palm oil, has shown interesting results [25][26][27]. These findings have established the potential of LC n3 PUFAs in combinations other than that of fish oil.…”
Section: Discussionmentioning
confidence: 99%